2009
DOI: 10.1016/j.ssc.2009.06.039
|View full text |Cite
|
Sign up to set email alerts
|

The enigma of the quantum Hall effect in graphene

Abstract: We apply Laughlin's gauge argument to analyze the ν = 0 quantum Hall effect observed in graphene when the Fermi energy lies near the Dirac point, and conclude that this necessarily leads to divergent bulk longitudinal resistivity in the zero temperature thermodynamic limit. We further predict that in a Corbino geometry measurement, where edge transport and other mesoscopic effects are unimportant, one should find the longitudinal conductivity vanishing in all graphene samples which have an underlying ν = 0 qua… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 57 publications
(58 reference statements)
1
22
0
Order By: Relevance
“…This n ¼ 0 state can hence be viewed as a pseudo-spin Hall insulator, if we consider the top and bottom degree of freedom as the pseudospin variable. Such an observation of a zero conductance plateau has been reported also in disordered graphene under very high magnetic field [23][24][25][26] and analysed theoretically 27 , as well as in the 2D TIs, the quantum wells of HgTe 28 and InAs/GaSb 29 . From the analyses shown in the following, we propose here that the major origin for the presence of s xy ¼ 0 is more like the energy difference of the top/bottom Dirac points rather than other effects such as electron-hole puddles due to composition inhomogeneity.…”
Section: Resultsmentioning
confidence: 54%
“…This n ¼ 0 state can hence be viewed as a pseudo-spin Hall insulator, if we consider the top and bottom degree of freedom as the pseudospin variable. Such an observation of a zero conductance plateau has been reported also in disordered graphene under very high magnetic field [23][24][25][26] and analysed theoretically 27 , as well as in the 2D TIs, the quantum wells of HgTe 28 and InAs/GaSb 29 . From the analyses shown in the following, we propose here that the major origin for the presence of s xy ¼ 0 is more like the energy difference of the top/bottom Dirac points rather than other effects such as electron-hole puddles due to composition inhomogeneity.…”
Section: Resultsmentioning
confidence: 54%
“…Similar behavior has been observed in monolayers 7 and in particle-hole symmetric semiconductor systems. 8 While this is unusual, it does not rule out quantum Hall physics, because Laughlin's gauge argument 9 connects a vanishing longitudinal conductivity σ xx to the quantized Hall conductivity σ xy , which is consistent 10 with a divergent ρ xx = ρ yy for ρ xy = 0. While Zhao et al 2 found that the gap at ν = 0 depends on the field as √ B ⊥ , as expected of Coulomb interaction effects, Feldman et al, 1 using high-mobility suspended samples, measured a gap that opens linearly with B ⊥ and hardly depends on B .…”
Section: Introductionmentioning
confidence: 99%
“…The nature of the electronic states at the N ¼ 0 LL at present remains unclear. While some theories predict unusual metallic transport via gapless edge states [6][7][8] other suggest that a gap may open at high magnetic fields, resulting in an insulating state near the charge-neutrality, n s ¼ 0, point (CNP) [9][10][11]. However, theories mainly focus on quantum Hall transport in the absence of strong electrostatic disorder, which, along with the Coulomb interaction, plays key role in defining the electron localization in 2DEGs [12][13][14][15][16][17][18][19].…”
mentioning
confidence: 99%